Composite artificial periosteum and preparation method thereof

By adopting a bilayer structure of composite artificial periosteum, combining the umbilical cord layer and the gel layer of bone-loading mineral material, the problem of insufficient bone induction ability in the prior art is solved, and better bone defect healing and regeneration effects are achieved.

CN116747354BActive Publication Date: 2025-03-14MOBILE MEDICAL TECH (SHANGHAI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310788170.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-03-14
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

In the prior art, the bone induction ability of artificial periosteum is insufficient and has a single function, making it difficult to effectively promote the healing and regeneration of bone defect sites.

Method used

Using a bilayer structure of composite artificial periosteum, the umbilical cord layer is composed of umbilical cord tissue, the gel layer is composed of chitosan and sodium alginate to form a hydrogel network, and is loaded with bone repair mineral materials silica, tricalcium phosphate and bioactive glass.

Benefits of technology

It improves the biocompatibility, mechanical properties and osteoinduction of the periosteum, enhances the binding force with bone tissue, and promotes the healing and regeneration of bone defect sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116747354B_ABST
    Figure CN116747354B_ABST
Patent Text Reader

Abstract

The present invention provides a composite artificial periosteum and a preparation method thereof, wherein the composite artificial periosteum comprises an umbilical cord layer and a gel layer; the umbilical cord layer is a sheet structure composed of umbilical cord tissue, wherein the umbilical cord tissue is formed from an umbilical cord from which vascular cells are mechanically removed; the gel layer is adhered to one side of the umbilical cord layer, wherein the gel layer is formed by a hydrogel network formed by a composite of chitosan and sodium alginate and loaded with bone repair mineral materials and freeze-dried, wherein the bone repair mineral materials are any one or two of silicon dioxide, tricalcium phosphate and bioactive glass. The artificial periosteum prepared by the present invention integrates barrier and repair, can play a protective role as a barrier membrane to prevent soft tissue invasion, can effectively guide bone regeneration, provide an excellent microenvironment for the regeneration and structural reconstruction of bone components, can induce bone repair and regeneration, and can be degraded synchronously with the reconstruction of new tissue, greatly improving the healing rate of bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a composite artificial periosteum and a preparation method thereof. Background Art

[0002] Bones are one of the important organs of the human body. Bone defects caused by exercise, trauma, and tumor resection have always been one of the common clinical diseases. In recent years, bone scaffold materials used in the field of bone repair have developed rapidly and have extremely broad development and application prospects. These scaffold materials based on the principle of bone tissue engineering temporarily serve as a bridge for the growth and proliferation of bone cells around the defect to connect with each other, inducing healing and regeneration of the bone defect. However, the ideal scaffold material needs to have good biocompatibility and no inflammatory response or cytotoxicity during implantation; it also needs to have excellent bone integration properties and mechanical properties that match bone tissue. At the same time, it also needs to have a pore structure that induces and promotes cell growth and migration.

[0003] The periosteum is a solid double-layer connective tissue capsule covering the bone surface except for the joints, which is divided into a fibrous layer and a germinal layer. The fibrous layer is mainly composed of thick collagen fiber bundles that interweave into a network, which plays a role in fixing the periosteum and ligaments. The germinal layer is close to the outer surface of the bone, has few fiber components, is loosely arranged, and has the ability to form bones, so it is also called the osteoblastic layer. As a physical barrier, although the periosteum cannot induce new bone formation by itself, it can provide a supportive microenvironment to promote the regeneration of new bone tissue, which is particularly important for the rapid healing of fractures and bone defects.

[0004] The Chinese patent with publication number CN114028619A discloses a double-layer artificial periosteum and its preparation method and application. The double-layer artificial periosteum includes: a dense layer and a loose layer. The dense layer is prepared from silk fibroin, and the loose layer is prepared from a composite material of selenium-doped hydroxyapatite and type I collagen. When used, the dense layer faces the soft tissue, and the loose layer faces the bone injury site. The double-layer periosteum of the above method is only close to the natural periosteum in structure, but has the problem of insufficient bone induction ability.

[0005] Therefore, it is necessary to provide a novel composite artificial periosteum and a preparation method thereof to solve the above-mentioned problems existing in the prior art. Summary of the invention

[0006] The purpose of the present invention is to provide a composite artificial periosteum and a preparation method thereof, which has good biocompatibility, no cytotoxicity, excellent mechanical properties, good interface bonding strength, and good osteoinductivity and mechanical properties, thereby improving the shortcomings of the existing artificial periosteum, such as insufficient induction ability and single function.

[0007] To achieve the above object, the composite artificial periosteum of the present invention comprises:

[0008] The cord layer is a sheet-like structure composed of umbilical cord tissue formed from the umbilical cord by mechanically removing vascular cells;

[0009] The gel layer is adhered to one side of the umbilical cord layer. The gel layer is formed by compounding chitosan and sodium alginate to form a hydrogel network and loading bone repair mineral material through freeze drying. The bone repair mineral material is any one or two of silicon dioxide, tricalcium phosphate and bioactive glass.

[0010] The beneficial effects of the composite artificial periosteum of the present invention are as follows: the gel layer is formed by a hydrogel network formed by a composite of chitosan and sodium alginate and loaded with bone repair mineral materials and freeze-dried, so that the porous structure of the scaffold is retained after freeze-drying, so that the gel layer can swell and retain a large amount of water, which is convenient for loading cells and factors, and has good osteogenic activity and mechanical properties; and the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed from an umbilical cord through which vascular cells are mechanically removed. The various natural active ingredients retained in the umbilical cord layer can improve the healing ability of the wound, and can also reduce the postoperative generation of scar; that is, the composite artificial periosteum has a double-layer membrane structure, one layer is a gel layer, sodium alginate and chitosan are natural polymer materials, which can form excellent properties such as interpenetrating or semi-interpenetrating networks in the hydrogel matrix, present a three-dimensional network structure after freeze-drying, and can still maintain integrity after being applied to the surface of tissue defects and swelling without deforming and shifting the membrane; silica, tricalcium phosphate and bioactive glass can not only enhance the mechanical properties of artificial periosteum, but also in the process of repairing bone tissue defects, silica, tricalcium phosphate and bioactive glass can interact with body fluids, thereby inducing the formation of bone apatite, so it has good osteogenic ability. The other layer of the artificial periosteum is the umbilical cord layer, which has a natural extracellular matrix structure and active factors, can effectively and quickly recruit cells in the contact area, induce osteogenic differentiation, promote vascularization, and provide a stable osteogenic environment. The artificial periosteum of the present invention has different surface morphologies and hierarchical porous structures, can simulate the unique microenvironment in the extracellular matrix of the periosteum, and provide various structures, mechanics and biological activities to improve the shortcomings of the existing artificial periosteum structure and single function. The present invention adopts the complementary advantages of allogeneic umbilical cord with good biocompatibility and sodium alginate and chitosan hydrogel network loaded with bone repair mineral materials, and the double-layer artificial periosteum prepared by freeze-drying is close to the structure and performance of natural periosteum. That is, the artificial periosteum prepared by the present invention integrates barrier and repair, and has the dual effects of good barrier and bone induction ability. It can not only play a protective role as a barrier membrane to prevent soft tissue invasion, but also effectively guide bone regeneration, provide an excellent microenvironment for the regeneration and structural reconstruction of bone components, can induce bone repair and regeneration, and can be synchronously degraded with the reconstruction of new tissue, greatly improving the healing rate of bone defects.

[0011] Further preferably, the bone repair mineral material is silicon dioxide. Its beneficial effects are: silicon dioxide can not only enhance the mechanical properties of artificial periosteum, but also make it have better bone formation ability; silicon is an essential trace element required for processes related to connective tissue development and bone metabolism, which helps to promote bone matrix deposition and mineralization and recruit mesenchymal stem cells in osteogenic differentiation, which is beneficial to hard tissue formation and mineralization; and in the process of repairing bone tissue defects, silicon dioxide materials can interact with body fluids to induce the formation of bone apatite, so it has better bone formation ability.

[0012] Further preferably, the bone repair mineral material is calcium phosphate and its complex, such as tricalcium phosphate. Its beneficial effects are: calcium phosphate and its complex have similar osteoinductivity and tissue compatibility as autologous bone, have the characteristics of stimulating the formation of new bone and capillaries, improving the nutritional status of local bone tissue, and can provide a scaffold for the formation of new bone.

[0013] Further preferably, the bone repair mineral material is bioactive glass. The beneficial effect is that the bioactive glass has high biological activity, bone binding and mechanical properties, so that the prepared gel layer scaffold can form a stronger interface with the surrounding hard and soft host bone tissues.

[0014] Preferably, the particle size of the bone repair mineral material is 20 μm to 100 μm. The beneficial effect is that if the particle size is too small, the material is prone to agglomeration, and if the particle size is too large, the subsequent silica material will not be used to generate hydroxyapatite when used.

[0015] Preferably, the thickness of the composite artificial periosteum is 1000 μm to 3000 μm. The beneficial effect is that the composite artificial periosteum has a certain degree of roughness and hydrophilicity, can be very tightly attached to the bone end and tendon to be repaired, and is conducive to the adhesion, proliferation and differentiation of cells.

[0016] Preferably, the pore size of the gel layer is 500 μm to 900 μm. The beneficial effect is that the larger pore size provides a sufficiently large space for oxygen and nutrient supply, which is conducive to mediating blood vessel formation to promote bone inductivity.

[0017] Preferably, the mass ratio of the sodium alginate, the chitosan and the bone repair mineral material is (5:5:1) to (4:2:1). The beneficial effect is that this mass ratio can make the gel layer have excellent mechanical properties and toughness, so that the composite artificial periosteum can provide structural support in the bone defect.

[0018] Preferably, the side of the umbilical cord layer facing away from the gel layer is a smooth surface, and the side of the gel layer facing away from the umbilical cord layer is an indentation surface, and the indentation surface is provided with a convex structure and a concave structure. Its beneficial effect is that the double-sided structure can fit well with the part to be repaired, provide a relatively closed tissue growth environment, provide a good space and time for bone regeneration, and promote tissue repair and regeneration. Among them, the convex structure and the concave structure of the indentation surface can effectively increase the degree of fit and contact surface area between the artificial periosteum and the part to be repaired, improve the fit between the artificial periosteum and the tissue defect, and improve clinical use and treatment effects. The artificial periosteum has an indentation surface and a smooth surface. The double-sided structure not only fits well with the bone tissue to be repaired, but also can selectively guide cell growth, and can be degraded synchronously with the reconstruction of the new tissue. The present invention solves the problem in the prior art that there is a gap between the biofilm with smooth surfaces on both sides and the tissue defect, causing fibroblasts and epithelial cells with faster growth and migration rates to enter the bone defect area, forming competitive inhibition with osteoblasts with slower growth and migration rates, and having an adverse effect on the healing of bone tissue.

[0019] Preferably, the gel layer and the umbilical cord layer are adhered and fixed by pressing and freeze-drying with a mold, and the mold includes a first surface and a second surface arranged oppositely, the first surface is an indentation surface adapted to the indentation surface, the indentation surface is provided with a convex structure and a concave structure, and the second surface is a smooth surface adapted to the smooth surface. Its beneficial effect is that: the artificial periosteum can be pressed and freeze-dried into two different structures on both sides by using the mold; that is, the indentation surface provided with the convex structure and the concave structure makes one surface of the artificial periosteum pressed and freeze-dried have a convex structure and a concave structure, so as to effectively increase the degree of fit and contact surface area between the biofilm and the part to be repaired, improve the fit between the biofilm medical material and the tissue defect, and improve the clinical use and treatment effect. It solves the problem in the prior art that there is a gap between the biofilm with smooth and flat surfaces on both sides and the tissue defect, causing fibroblasts and epithelial cells with faster growth and migration rates to enter the bone defect area, forming competitive inhibition with osteoblasts with slower growth and migration rates, and having an adverse effect on the healing of bone tissue.

[0020] Preferably, the umbilical cord layer is a double-layer porous structure, the umbilical cord layer includes a dense layer and a loose layer, the pore size of the dense layer is smaller than the pore size of the loose layer, the loose layer is adhered and fixed to the gel layer, and the dense layer is provided with the smooth surface. Its beneficial effect is that: the artificial periosteum is used to be placed on the surface of damaged bone tissue to create a relatively closed bone regeneration environment; therefore, the dense layer with a small pore size can block the fibroblasts and epithelial cells with a faster migration speed from entering the bone defect area toward the bone tissue to play a barrier role; compared with the two different layers of the double-layer membrane structure in the prior art, which are simply fixed by pressing, the loose layer in the present invention is bonded to the gel layer, and through freeze-thaw treatment, the gel layer is adsorbed into the micropores of the loose layer of the umbilical cord layer, so that the adhesion between the gel layer and the umbilical cord layer is enhanced, that is, the bonding force between the fitting interface is greatly improved, and the problem of insufficient bonding between the membrane layers and easy stratification in the prior art is solved.

[0021] Preferably, the pore size of the loose layer is 20 μm to 100 μm. Its beneficial effects are: the umbilical cord itself is a natural double-sided structure, and the dense layer retains the natural collagen fiber dense structure of the umbilical cord, which is used to face the bone tissue, and can effectively prevent fibroblasts and epithelial cells from growing into the bone defect area, support bone tissue formation, and prevent soft tissue from growing into the bone defect area; the collagen arrangement of the loose layer is relatively sparse, and has a certain pore size, which can achieve a tight combination with the gel layer in some areas during the freeze-thaw process, and realize the preparation of a double-layer membrane without stratification after rehydration, so that when applied to bone tissue defects, the dense layer and the loose layer can effectively play their respective roles.

[0022] Preferably, the umbilical cord is an allogeneic umbilical cord. Its beneficial effects are: the allogeneic umbilical cord has a porous double-layer structure, one layer of collagen fibers is densely arranged, and the other layer of collagen fibers is relatively loosely arranged; it contains a variety of bioactive ingredients, has low immunogenicity, and promotes cell attachment and tissue regeneration and healing. The unique biological characteristics are of great significance in clinical applications.

[0023] It is further preferred that the umbilical cord tissue is derived from the human body. Its beneficial effects are: the use of human umbilical cord tissue as the basal layer breaks the limitation of preparing artificial periosteum with animal-derived raw materials, and can effectively avoid rejection reactions in patients; the umbilical cord contains basic fibroblast growth factor, insulin-like growth factor, platelet-derived growth factor and transforming growth factor, etc., which can be used as a sustained-release carrier of growth factors to promote cell proliferation and osteogenic activity; and the human umbilical cord has low immunogenicity, and the natural active ingredients are mainly composed of collagen, glycoprotein, mucopolysaccharide and growth factor, which can not only provide cells with a bionic three-dimensional support carrier, but also promote the migration, proliferation and differentiation of host cells through various proteins and growth factors interacting with the host to promote tissue regeneration and repair. The umbilical cord layer is derived from human umbilical cord tissue from which vascular cells are mechanically removed, and the cell matrix is ​​removed, and the main component is collagen. Human umbilical cord tissue is often considered "medical waste", and its application cost is correspondingly lower.

[0024] The method for preparing the composite artificial periosteum of the present invention comprises the steps of:

[0025] Sodium alginate, chitosan and bone repair mineral materials are prepared into hydrogel by combining semi-dissolving acidified sol-gel transition method and internal gel method, and then vacuum freeze-dried after removing bubbles by ultrasonic to obtain gel layer;

[0026] Providing an original umbilical cord, removing blood vessels in the original umbilical cord by mechanical means to form umbilical cord tissue to be shaped, and trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet-like structure;

[0027] The gel layer is adhered and fixed to the umbilical cord layer to obtain the composite artificial periosteum.

[0028] The beneficial effects of the composite artificial periosteum preparation method of the present invention are: a hydrogel is prepared by combining a semi-dissolving acidified sol-gel transition method and an internal gel method with sodium alginate, chitosan and a bone repair mineral material, and a gel layer is prepared by vacuum freeze-drying after removing bubbles by ultrasonication; an original umbilical cord is provided, blood vessels in the original umbilical cord are mechanically removed to form an umbilical cord tissue to be shaped, and the umbilical cord tissue to be shaped is trimmed into an umbilical cord layer with a sheet structure; the gel layer is adhered and fixed to the umbilical cord layer to prepare the composite artificial periosteum. The preparation method is simple, so that the prepared The composite artificial periosteum has a double-layer membrane structure, one layer is a gel layer, sodium alginate and chitosan are natural polymer materials, and can form excellent properties such as interpenetrating or semi-interpenetrating networks in the hydrogel matrix, present a three-dimensional network structure after freeze-drying, and can still maintain integrity after being applied to the surface of tissue defects and swelling without deforming and shifting the membrane; silica, tricalcium phosphate and bioactive glass can not only enhance the mechanical properties of the artificial periosteum, but also in the process of repairing bone tissue defects, silica, tricalcium phosphate and bioactive glass can interact with body fluids, thereby inducing the formation of bone apatite, so it has good osteogenic ability. The other layer of the artificial periosteum is the umbilical cord layer, which has a natural extracellular matrix structure and active factors, can effectively and quickly recruit cells at the contact site, induce osteogenic differentiation, promote vascularization, and provide a stable osteogenic environment. The artificial periosteum of the present invention has different surface morphologies and hierarchical porous structures, can simulate the unique microenvironment in the extracellular matrix of the periosteum, and provide various structures, mechanics and biological activities to improve the shortcomings of the existing artificial periosteum structure and single function. The present invention adopts the complementary advantages of allogeneic umbilical cord with good biocompatibility and sodium alginate and chitosan hydrogel network loaded with bone repair mineral materials, and the double-layer artificial periosteum prepared by freeze-drying is close to the structure and performance of natural periosteum. That is, the artificial periosteum prepared by the present invention integrates barrier and repair, and has the dual effects of good barrier and bone induction ability. It can not only play a protective role as a barrier membrane to prevent soft tissue invasion, but also effectively guide bone regeneration, provide an excellent microenvironment for the regeneration and structural reconstruction of bone components, can induce bone repair and regeneration, and can be synchronously degraded with the reconstruction of new tissue, greatly improving the healing rate of bone defects.

[0029] Preferably, the step of preparing the hydrogel by combining the semi-dissolving acidified sol-gel transition method and the internal gel method with sodium alginate, chitosan and the bone repair mineral material comprises:

[0030] Adding the bone repair mineral material into deionized water and stirring to prepare a bone repair mineral solution;

[0031] Adding the sodium alginate and the chitosan to the bone repair mineral solution in sequence, and stirring to mix them evenly to obtain a sol solution;

[0032] The sol solution is exposed to an acidic environment for gelation to obtain the hydrogel. The beneficial effect is that when the acidic vapor in the acidic environment diffuses to the surface and the interior of the sol solution, the chitosan is slowly protonated, so that it can form a physically cross-linked chitosan / sodium alginate hydrogel network with sodium alginate through electrostatic interaction, thereby avoiding the formation of uneven precipitates and gel.

[0033] Preferably, the step of adhering and fixing the gel layer to the umbilical cord layer to obtain the composite artificial periosteum comprises:

[0034] In an environment with a temperature of 11°C to 15°C, one side of the dense layer in the umbilical cord layer is covered on the smooth surface of the mold, one side of the gel layer is adhered to one side of the loose layer in the umbilical cord layer, and the other indentation surface of the mold is covered on the other side of the gel layer. The beneficial effects are as follows: the processing environment temperature of the umbilical cord layer is 11°C to 15°C, that is, rapid processing in a low-temperature environment can retain the natural active ingredients of the umbilical cord to the greatest extent; after being pressed and freeze-dried by the mold, the artificial periosteum presents a double-sided structure with an indented surface and a smooth surface, and the loose layer of the sheet umbilical cord layer is bonded to the gel layer, and then through subsequent freeze-thaw cycles and vacuum freeze-drying treatments, the loose layer and the gel layer can be more deeply combined, without obvious stratification, and the structural continuity is good; the surface of the part to be repaired usually has poor flatness, and the presence of the indentation structure can effectively increase the degree of fit between the artificial periosteum and the part to be repaired and the contact surface area, which is beneficial to promoting tissue healing; and the gel layer with bone repair mineral material covers the indentation surface of the mold, even if the gel layer has an indentation surface, so that the indentation surface of the gel layer with bone repair mineral material faces the bone defect, which can simultaneously improve the survival rate of osteoblasts and the amount of bone mineralization.

[0035] Preferably, the step of adhering and fixing the gel layer to the umbilical cord layer to obtain the composite artificial periosteum further comprises a normal pressure freeze-thaw cycle step and a vacuum freeze-drying step;

[0036] The normal pressure freeze-thaw cycle step comprises: freezing the mold sandwiched with the umbilical cord layer and the gel layer at a temperature not higher than -22°C for not less than 2 hours at normal pressure, and then freezing and thawing at a temperature not higher than 10°C for not less than 2 hours, and performing freeze-thaw cycles 1-3 times to obtain a periosteum sample;

[0037] The vacuum freeze drying step includes: placing the periosteum sample in a vacuum freeze dryer, cooling to -80±5°C at a rate of 5°C / min to 10°C / min, and the vacuum freeze drying time is not less than 8h to obtain the composite artificial periosteum. Its beneficial effect is that: through freeze-thaw treatment, the gel layer can be adsorbed into the micropores of the loose layer of the umbilical cord layer, so that the adhesion between the gel layer and the umbilical cord layer is enhanced, that is, the bonding force between the fitting interface is greatly improved, and the problem of insufficient bonding between the membrane layers and easy stratification in the prior art is solved; wherein in the vacuum freeze drying process, by slowly cooling to -80±5°C at a rate of 5°C / min to 10°C / min, it is possible to avoid the destruction of the tissue structure caused by too fast a temperature drop, thereby retaining the double-layer porous structure of the umbilical cord tissue.

[0038] Preferably, the steps of covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer are repeated, and 2 to 6 layers of the umbilical cord layer and the gel layer are stacked in the stacking order of the mold, the umbilical cord layer, the gel layer and another mold to obtain 2 to 6 layers of the artificial periosteum. Its beneficial effect is that the number of stacked layers of the artificial periosteum is generally 2 to 6 layers, which avoids the excessive weight of the mold causing the artificial periosteum to be freeze-dried to be deformed by compression, while reducing the energy consumption required for freeze-drying. The artificial periosteum obtained after compression and freeze-drying has two structures, an indentation surface and a smooth surface. The indentation surface can fit tightly with the tissue defect, blocking the growth of external soft tissue cells, and achieving a good therapeutic effect.

[0039] Preferably, the step of trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure comprises:

[0040] In an environment with a temperature of 11°C to 15°C, the umbilical cord tissue to be shaped is washed with a washing liquid, trimmed into sheets and washed with deionized water for 1 to 3 times to obtain the umbilical cord layer, and the washing temperature is 11°C to 15°C, and the washing time is 15 to 20 minutes. The beneficial effect is that the umbilical cord tissue is washed with a washing liquid to wash away blood stains and damaged cells, and is rinsed with deionized water to keep the umbilical cord layer moist for easy adhesion to the gel layer. By setting the processing environment temperature of the umbilical cord layer to 11°C to 15°C and the washing time to 15 to 20 minutes, the umbilical cord layer is quickly processed in a low temperature environment to retain the natural active ingredients of the umbilical cord to the greatest extent.

[0041] Preferably, the cleaning solution for the umbilical cord tissue is any one or more of sterile physiological phosphate buffer solution, sterile sodium chloride injection and purified water. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1It is a schematic diagram of a longitudinal section of a double-layer structure of a composite artificial periosteum according to an embodiment of the present invention, obtained by electron microscope scanning;

[0043] Figure 2 A schematic diagram of a mold according to a first embodiment of the present invention;

[0044] Figure 3 is a schematic diagram of a mold according to a second embodiment of the present invention;

[0045] Figure 4 for Figure 3 An enlarged schematic diagram of the structure of the surface of the first layer of the mold shown;

[0046] Figure 5 for Figure 3 An enlarged schematic diagram of the structure of the surface of the second layer in the mold is shown. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0048] In addition, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. All reagents or instruments without manufacturer specified are common commercial products and can be purchased on the market.

[0049] In order to overcome the problems existing in the prior art, the embodiments of the present invention provide a composite artificial periosteum and a preparation method thereof, which has good biocompatibility, no cytotoxicity, excellent mechanical properties, good interface bonding strength, and good osteoinductivity and mechanical properties, thereby improving the shortcomings of the existing artificial periosteum, such as insufficient induction ability and single function.

[0050] To achieve the above object, the composite artificial periosteum of the present invention comprises:

[0051] The cord layer is a sheet-like structure composed of umbilical cord tissue formed from the umbilical cord by mechanically removing vascular cells;

[0052] The gel layer is adhered to one side of the umbilical cord layer. The gel layer is formed by compounding chitosan and sodium alginate to form a hydrogel network and loading bone repair mineral material through freeze drying. The bone repair mineral material is any one or two of silicon dioxide, tricalcium phosphate and bioactive glass.

[0053] The beneficial effects of the composite artificial periosteum of the present invention are as follows: the gel layer is formed by a hydrogel network formed by a composite of chitosan and sodium alginate and loaded with bone repair mineral materials and freeze-dried, so that the porous structure of the scaffold is retained after freeze-drying, so that the gel layer can swell and retain a large amount of water, which is convenient for loading cells and factors, and has good osteogenic activity and mechanical properties; and the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed from an umbilical cord through which vascular cells are mechanically removed. The various natural active ingredients retained in the umbilical cord layer can improve the healing ability of the wound, and can also reduce the postoperative generation of scar; that is, the composite artificial periosteum has a double-layer membrane structure, one layer is a gel layer, sodium alginate and chitosan are natural polymer materials, which can form excellent properties such as interpenetrating or semi-interpenetrating networks in the hydrogel matrix, present a three-dimensional network structure after freeze-drying, and can still maintain integrity after being applied to the surface of tissue defects and swelling without deforming and shifting the membrane; silica, tricalcium phosphate and bioactive glass can not only enhance the mechanical properties of artificial periosteum, but also in the process of repairing bone tissue defects, silica, tricalcium phosphate and bioactive glass can interact with body fluids, thereby inducing the formation of bone apatite, so it has good osteogenic ability. The other layer of the artificial periosteum is the umbilical cord layer, which has a natural extracellular matrix structure and active factors, can effectively and quickly recruit cells in the contact area, induce osteogenic differentiation, promote vascularization, and provide a stable osteogenic environment. The artificial periosteum of the present invention has different surface morphologies and hierarchical porous structures, can simulate the unique microenvironment in the extracellular matrix of the periosteum, and provide various structures, mechanics and biological activities to improve the shortcomings of the existing artificial periosteum structure and single function. The present invention adopts the complementary advantages of allogeneic umbilical cord with good biocompatibility and sodium alginate and chitosan hydrogel network loaded with bone repair mineral materials, and the double-layer artificial periosteum prepared by freeze-drying is close to the structure and performance of natural periosteum. That is, the artificial periosteum prepared by the present invention integrates barrier and repair, and has the dual effects of good barrier and bone induction ability. It can not only play a protective role as a barrier membrane to prevent soft tissue invasion, but also effectively guide bone regeneration, provide an excellent microenvironment for the regeneration and structural reconstruction of bone components, can induce bone repair and regeneration, and can be synchronously degraded with the reconstruction of new tissue, greatly improving the healing rate of bone defects.

[0054] In some specific embodiments of the present invention, the bone repair mineral material is silicon dioxide. Silicon dioxide can not only enhance the mechanical properties of artificial periosteum, but also make it have better bone formation ability; silicon is an essential trace element required for processes related to connective tissue development and bone metabolism, which helps to promote bone matrix deposition and mineralization and recruit mesenchymal stem cells in osteogenic differentiation, which is beneficial to hard tissue formation and mineralization; and in the process of repairing bone tissue defects, silicon dioxide materials can interact with body fluids to induce the formation of bone apatite, so they have better bone formation ability.

[0055] In some specific embodiments of the present invention, the bone repair mineral material is calcium phosphate and its complex, such as tricalcium phosphate. Calcium phosphate and its complex have similar osteoinductivity and tissue compatibility as autologous bone, have the characteristics of stimulating the formation of new bone and capillaries, and improving the nutritional status of local bone tissue, and can provide a scaffold for the formation of new bone.

[0056] In some specific embodiments of the present invention, the bone repair mineral material is bioactive glass. Bioactive glass has high biological activity, bone binding, and mechanical properties, so that the prepared gel layer scaffold can form a stronger interface with the surrounding hard and soft host bone tissues.

[0057] In some embodiments of the present invention, the particle size of the bone repair mineral material is 20 μm to 100 μm. If the particle size is too small, the material is prone to agglomeration, and if the particle size is too large, the subsequent silica material will not be used to generate hydroxyapatite when used.

[0058] In some specific embodiments of the present invention, the particle size of the silicon dioxide is any one of 25 μm, 30 μm, 40 μm, 50 μm, 55 μm, 65 μm, 70 μm, 75 μm, 80 μm, 90 μm and 95 μm.

[0059] In some embodiments of the present invention, the thickness of the composite artificial periosteum is 1000 μm to 3000 μm, so that the composite artificial periosteum has a certain degree of roughness and hydrophilicity, and can be very tightly attached to the bone end and tendon to be repaired, which is conducive to the adhesion, proliferation and differentiation of cells.

[0060] In some specific embodiments of the present invention, the thickness of the composite artificial periosteum is any one of 1000 μm, 1050 μm, 1100 μm, 1250 μm, 1500 μm, 1700 μm, 2000 μm, 2250 μm, 2450 μm, 2600 μm, 2800 μm, 2900 μm and 2950 μm.

[0061] In some embodiments of the present invention, the pore size of the gel layer is 500 μm to 900 μm. A larger pore size provides a sufficiently large space for oxygen and nutrient supply, which is beneficial for mediating blood vessel formation to promote bone inductivity.

[0062] In some specific embodiments of the present invention, the pore size of the gel layer is any one of 550 μm, 600 μm, 650 μm, 680 μm, 700 μm, 720 μm, 750 μm, 780 μm, 800 μm, 850 μm, 875 μm and 890 μm.

[0063] In some embodiments of the present invention, the mass ratio of the sodium alginate, the chitosan and the bone repair mineral material is (5:5:1) to (4:2:1). This mass ratio can make the gel layer have excellent mechanical properties and toughness, so that the composite artificial periosteum can provide structural support in the bone defect.

[0064] In some embodiments of the present invention, the side of the umbilical cord layer facing away from the gel layer is a smooth surface, and the side of the gel layer facing away from the umbilical cord layer is an indentation surface, and the indentation surface is provided with a convex structure and a concave structure. The double-sided structure can fit well with the part to be repaired, provide a relatively closed tissue growth environment, provide a good space and time for bone regeneration, and promote tissue repair and regeneration. Among them, the convex structure and the concave structure of the indentation surface can effectively increase the degree of fit and contact surface area between the artificial periosteum and the part to be repaired, improve the fit between the artificial periosteum and the tissue defect, and improve clinical use and treatment effects. The artificial periosteum has an indentation surface and a smooth surface. The double-sided structure not only fits well with the bone tissue to be repaired, but also can selectively guide cell growth, and can be degraded synchronously with the reconstruction of the new tissue. The present invention solves the problem in the prior art that there is a gap between the biofilm with smooth surfaces on both sides and the tissue defect, causing fibroblasts and epithelial cells with faster growth and migration rates to enter the bone defect area, forming competitive inhibition with osteoblasts with slower growth and migration rates, and having an adverse effect on the healing of bone tissue.

[0065] In some embodiments of the present invention, the gel layer and the umbilical cord layer are adhered and fixed by pressing and freeze-drying with a mold, and the mold includes a first surface and a second surface arranged oppositely, the first surface is an indentation surface adapted to the indentation surface, the indentation surface is provided with a convex structure and a concave structure, and the second surface is a smooth surface adapted to the smooth surface. The mold can be used to press and freeze-dry the artificial periosteum into two sides with different structures; that is, the indentation surface provided with the convex structure and the concave structure makes one surface of the artificial periosteum pressed and freeze-dried have a convex structure and a concave structure, so as to effectively increase the degree of fit between the biofilm and the part to be repaired and the contact surface area, improve the fit between the biofilm medical material and the tissue defect, and improve the clinical use and treatment effect. The problem that there is a gap between the biofilm with smooth and flat surfaces on both sides and the tissue defect in the prior art is solved, causing fibroblasts and epithelial cells with faster growth and migration rates to enter the bone defect area, forming competitive inhibition with osteoblasts with slower growth and migration rates, and having an adverse effect on the healing of bone tissue.

[0066] In some embodiments of the present invention, the umbilical cord layer is a double-layer porous structure, the umbilical cord layer includes a dense layer and a loose layer, the pore size of the dense layer is smaller than the pore size of the loose layer, the loose layer is adhered and fixed to the gel layer, and the dense layer is provided with the smooth surface. Artificial periosteum is used to be placed on the surface of damaged bone tissue to create a relatively closed bone regeneration environment; therefore, the dense layer with a small pore size facing the bone tissue can block the fibroblasts and epithelial cells with faster migration speed from entering the bone defect area to play a barrier role; compared with the two different layers of the double-layer membrane structure in the prior art, which are simply fixed by pressing, the loose layer in the present invention is bonded to the gel layer, and through freeze-thaw treatment, the gel layer is adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, that is, greatly improving the bonding force between the fitting interfaces, solving the problem of insufficient bonding between the membrane layers and easy stratification in the prior art.

[0067] In some embodiments of the present invention, the pore size of the loose layer is 20 μm to 100 μm. The umbilical cord itself is a natural double-sided structure, and the dense layer retains the natural collagen fiber dense structure of the umbilical cord, which is used to face the bone tissue, and can effectively prevent fibroblasts and epithelial cells from growing into the bone defect area, support bone tissue formation, and prevent soft tissue from growing into the bone defect area; the collagen arrangement of the loose layer is relatively sparse, and has a certain pore size, which can achieve a tight combination with the gel layer in some areas during the freeze-thaw process, and realize the preparation of a double-layer membrane without stratification after rehydration, so that when applied to bone tissue defects, the dense layer and the loose layer can effectively play their respective roles.

[0068] In some embodiments of the present invention, the umbilical cord is an allogeneic umbilical cord. Allogeneic umbilical cord has a porous double-layer structure, one layer of collagen fibers is densely arranged, and the other layer of collagen fibers is relatively loosely arranged; it contains a variety of bioactive ingredients, has low immunogenicity, and promotes cell attachment and tissue regeneration and healing. The unique biological characteristics are of great significance in clinical applications.

[0069] In some embodiments of the present invention, the umbilical cord tissue is derived from the human body. The use of human umbilical cord tissue as the basal layer breaks the limitation of using animal-derived raw materials to prepare artificial periosteum, and can effectively avoid rejection reactions in patients; the umbilical cord contains basic fibroblast growth factor, insulin-like growth factor, platelet-derived growth factor and transforming growth factor, etc., which can be used as a sustained-release carrier of growth factors to promote cell proliferation and osteogenic activity; and the human umbilical cord has low immunogenicity, and the natural active ingredients are mainly composed of collagen, glycoprotein, mucopolysaccharide and growth factors, which can not only provide cells with a bionic three-dimensional support carrier, but also promote the migration, proliferation and differentiation of host cells through various proteins and growth factors interacting with the host to promote tissue regeneration and repair. The umbilical cord layer is derived from human umbilical cord tissue from which vascular cells are mechanically removed, and the cell matrix is ​​removed, and the main component is collagen. Human umbilical cord tissue is often considered "medical waste", and its application cost is correspondingly lower.

[0070] In some embodiments of the present invention, the method for preparing the composite artificial periosteum comprises the steps of:

[0071] Sodium alginate, chitosan and bone repair mineral materials are prepared into hydrogel by combining semi-dissolving acidified sol-gel transition method and internal gel method, and then vacuum freeze-dried after removing bubbles by ultrasonic to obtain gel layer;

[0072] Providing an original umbilical cord, removing blood vessels in the original umbilical cord by mechanical means to form umbilical cord tissue to be shaped, and trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet-like structure;

[0073] The gel layer is adhered and fixed to the umbilical cord layer to obtain the composite artificial periosteum.

[0074] Specifically, the composite artificial periosteum preparation method is simple, so that the composite artificial periosteum prepared has a double-layer membrane structure, one layer is a gel layer, sodium alginate and chitosan are natural polymer materials, and can form excellent properties such as interpenetrating or semi-interpenetrating networks in the hydrogel matrix, present a three-dimensional network structure after freeze-drying, and can still maintain integrity after being applied to the surface of tissue defects and swelling without deforming and shifting the membrane; silica, tricalcium phosphate and bioactive glass can not only enhance the mechanical properties of artificial periosteum, but also in the process of repairing bone tissue defects, silica, tricalcium phosphate and bioactive glass can interact with body fluids, thereby inducing the formation of bone apatite, so it has good osteogenic ability. The other layer of the artificial periosteum is the umbilical cord layer, which has a natural extracellular matrix structure and active factors, can effectively and quickly recruit cells at the contact site, induce osteogenic differentiation, promote vascularization, and provide a stable osteogenic environment. The artificial periosteum of the present invention has different surface morphologies and hierarchical porous structures, can simulate the unique microenvironment in the extracellular matrix of the periosteum, and provide various structures, mechanics and biological activities to improve the shortcomings of the existing artificial periosteum structure and single function. The present invention adopts the complementary advantages of the allogeneic umbilical cord with good biocompatibility and the sodium alginate and chitosan hydrogel network loaded with bone repair mineral materials, and the double-layer artificial periosteum prepared by freeze-drying is close to the natural periosteum structure and performance. That is, the artificial periosteum prepared by the present invention integrates barrier and repair as one, and has the dual effects of good barrier and bone induction ability. It can not only play a protective role as a barrier membrane to prevent soft tissue invasion, but also effectively guide bone regeneration, provide an excellent microenvironment for the regeneration and structural reconstruction of bone components, can induce bone repair and regeneration, and can be synchronously degraded with the reconstruction of new tissue, greatly improving the healing rate of bone defects.

[0075] Among them, the semi-dissolving acidified sol-gel transition method and the inner gel method are commonly used methods for preparing hydrogels or super-hydrophobic surfaces, which are conventional techniques in the field and will not be described in detail here.

[0076] In some embodiments of the present invention, the step of obtaining the gel layer by vacuum freeze drying comprises: placing the hydrogel from which bubbles have been removed in a vacuum freeze dryer at a temperature of -80±5°C for freeze drying for 10 h to 24 h to obtain the gel layer.

[0077] In some embodiments of the present invention, the step of preparing a hydrogel by combining a semi-dissolving acidified sol-gel transition method and an internal gel method with sodium alginate, chitosan and a bone repair mineral material comprises:

[0078] Adding the bone repair mineral material into deionized water and stirring to prepare a bone repair mineral solution;

[0079] Adding the sodium alginate and the chitosan to the bone repair mineral solution in sequence, and stirring to mix them evenly to obtain a sol solution;

[0080] The sol solution is exposed to an acidic environment for gelation to obtain the hydrogel. When the acidic vapor in the acidic environment diffuses to the surface and the interior of the sol solution, the chitosan is slowly protonated, so that it can form a physically cross-linked chitosan / sodium alginate hydrogel network with sodium alginate through electrostatic interaction, thereby avoiding the formation of uneven precipitates and gel. The physical cross-linking method for preparing hydrogels is simple in synthesis and has excellent biosafety.

[0081] The semi-dissolving and acidifying step refers to the step of exposing the sol solution in the sol state to an acidic environment for gelation. The sol solution is a liquefied semi-fluid state with properties similar to a fluid, and the hydrogel is a semi-solid state.

[0082] In some embodiments of the present invention, the acidic environment is formed by volatilizing an acetic acid solution.

[0083] In some embodiments of the present invention, the step of sequentially adding the sodium alginate and the chitosan to the bone repair mineral solution and stirring to mix evenly to obtain a sol solution includes: adding the sodium alginate to the bone repair mineral solution and stirring for 1 hour to 2 hours until it is dissolved, then adding the chitosan under stirring conditions, and continuously stirring for 1 hour to 4 hours to mix evenly to obtain a sol solution.

[0084] In some embodiments of the present invention, the step of adhering and fixing the gel layer to the umbilical cord layer to obtain the composite artificial periosteum comprises:

[0085] In an environment with a temperature of 11°C to 15°C, one side of the dense layer in the umbilical cord layer is covered on the smooth surface of the mold, one side of the gel layer is adhered to one side of the loose layer in the umbilical cord layer, and the other indentation surface of the mold is covered on the other side of the gel layer. The processing environment temperature of the umbilical cord layer is 11°C to 15°C, that is, rapid processing in a low-temperature environment can retain the natural active ingredients of the umbilical cord to the greatest extent; after being pressed and freeze-dried by the mold, the artificial periosteum presents a double-sided structure with an indented surface and a smooth surface, and the loose layer of the sheet umbilical cord layer is bonded to the gel layer, and then through subsequent freeze-thaw cycles and vacuum freeze-drying treatment, the loose layer and the gel layer can be more deeply integrated, without obvious stratification, and the structural continuity is good; the surface of the part to be repaired is usually not smooth, and the presence of the indentation structure can effectively increase the degree of fit and contact surface area between the artificial periosteum and the part to be repaired, which is beneficial to promoting tissue healing; and the gel layer with bone repair mineral material covers the indentation surface of the mold, even if the gel layer has an indentation surface, so that the indentation surface of the gel layer with bone repair mineral material faces the bone defect, which can simultaneously improve the survival rate of osteoblasts and the amount of bone mineralization.

[0086] Specifically, one side of the dense layer in the first umbilical cord layer is covered on the smooth surface of the first mold, one side of the first gel layer is tightly adhered to one side of the loose layer of the first umbilical cord layer, and then the indentation surface of the second mold is covered on the other side of the first gel layer; that is, two molds are used to press the umbilical cord layer and the gel layer in the same composite artificial periosteum; using the above-mentioned stacking method, 2-6 sheets of the composite artificial periosteum can be obtained by stacking and pressing 3 to 7 molds layer by layer.

[0087] In some specific embodiments of the present invention, one side of the dense layer in the first umbilical cord layer is covered on the smooth surface of the first mold, one side of the first gel layer is tightly adhered to one side of the loose layer of the first umbilical cord layer, and the indentation surface of the second mold is covered on the other side of the first gel layer, one side of the dense layer in the second umbilical cord layer is covered on the smooth surface of the second mold, one side of the second gel layer is tightly adhered to one side of the loose layer of the second umbilical cord layer, and the indentation surface of the third mold is covered on the other side of the second gel layer. In this way, two sheets of the composite artificial periosteum can be made using three molds.

[0088] In some embodiments of the present invention, the step of adhering and fixing the gel layer to one side of the umbilical cord layer to obtain the composite artificial periosteum further comprises a normal pressure freeze-thaw cycle step and a vacuum freeze-drying step;

[0089] The normal pressure freeze-thaw cycle step comprises: freezing the mold sandwiched with the umbilical cord layer and the gel layer at a temperature not higher than -22°C for not less than 2 hours at normal pressure, and then freezing and thawing at a temperature not higher than 10°C for not less than 2 hours, and performing freeze-thaw cycles 1-3 times to obtain a periosteum sample;

[0090] The vacuum freeze drying step includes: placing the periosteum sample in a vacuum freeze dryer, cooling it to -80±5°C at a rate of 5°C / min to 10°C / min, and the vacuum freeze drying time is not less than 8 hours to obtain the composite artificial periosteum. Through freeze-thaw treatment, the gel layer can be adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, that is, greatly improving the bonding force between the fitting interface, solving the problem of insufficient bonding between the membrane layers and easy stratification in the prior art; wherein during the vacuum freeze drying process, by cooling to -80±5°C at a rate of 5°C / min to 10°C / min, it is possible to avoid excessive temperature drop and tissue structure damage, thereby retaining the double-layer porous structure in the umbilical cord tissue.

[0091] In some embodiments of the present invention, the steps of covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer are repeated, and 2 to 6 layers of the umbilical cord layer and the gel layer are stacked in the stacking order of the mold, the umbilical cord layer, the gel layer and another mold to obtain 2 to 6 layers of artificial periosteum. The number of stacked layers of the artificial periosteum is generally 2 to 6 layers, so as to avoid the artificial periosteum to be freeze-dried being deformed by the excessive weight of the mold, and reduce the energy consumption required for freeze-drying. The artificial periosteum obtained after compression and freeze-drying has two structures, an indentation surface and a smooth surface. The indentation surface can fit tightly with the tissue defect, blocking the growth of external soft tissue cells, and achieving a good therapeutic effect.

[0092] In some embodiments of the present invention, the step of trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure comprises:

[0093] In an environment with a temperature of 11°C to 15°C, the umbilical cord tissue to be shaped is washed with a washing liquid, trimmed into sheets and washed with deionized water for 1 to 3 times to obtain the umbilical cord layer, and the washing temperature is 11°C to 15°C, and the washing time is 15 to 20 minutes. The umbilical cord tissue is washed with a washing liquid to wash away blood stains and damaged cells, and is rinsed with deionized water to keep the umbilical cord layer moist for easy adhesion to the gel layer. The processing environment temperature of the umbilical cord layer is set to 11°C to 15°C, and the washing time is 15 to 20 minutes, that is, the umbilical cord layer is quickly processed in a low temperature environment to retain the natural active ingredients of the umbilical cord to the greatest extent.

[0094] In some embodiments of the present invention, the cleaning solution for the umbilical cord tissue is any one or more of a sterile physiological phosphate buffer solution, a sterile sodium chloride injection solution and purified water.

[0095] Example 1

[0096] The preparation method of the composite artificial periosteum comprises the following steps:

[0097] S1. Preparation of umbilical cord layer:

[0098] S11. Select the original umbilical cord donated by a healthy pregnant woman and wash it 2-3 times with 0.9% sodium chloride cleaning solution until there is no blood stain;

[0099] S12, selecting annular drill bits with different inner diameters according to the diameters of the blood vessels to remove the blood vessels in the original umbilical cord to obtain the umbilical cord tissue to be reshaped;

[0100] S13, cutting the umbilical cord into a flat sheet along the axial direction of the umbilical cord, so as to trim the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure;

[0101] S14, soaking and moistening the umbilical cord layer with deionized water for later use;

[0102] S2. Preparation of gel layer:

[0103] S21, weigh 0.3 g of silicon dioxide, add it to 100 mL of deionized water and stir, then add 1.0 g of sodium alginate and stir for 1 h to 2 h until dissolved, add 0.6 g of chitosan under stirring, continue stirring for 1 h to 4 h to mix evenly to obtain a sol solution;

[0104] S22, centrifuging the sol at a speed of 500 rpm to 8000 rpm for 5 min to 10 min to remove bubbles for later use;

[0105] S23, pouring the slurry mixture from which bubbles have been removed into a 2 mm to 10 mm deep container, placing the container in a sealed plastic box containing 100 mL of acetic acid solution, performing sol-gel transition treatment for 12 h to 24 h, demolding and rinsing with deionized water to obtain a solid hydrogel; wherein the acetic acid solution is not immersed in the container, and acts by volatilization of the acetic acid solution;

[0106] S24, placing the hydrogel in a vacuum freeze dryer at -80°C for freeze drying for 10 h to 24 h to obtain a sponge-like gel layer;

[0107] S25, soaking and moistening the gel layer with deionized water for later use;

[0108] S3. Preparation of composite artificial periosteum:

[0109] S31, covering one side of the dense layer in the umbilical cord layer obtained in step S1 on the smooth surface of the first mold, tightly adhering one side of the gel layer obtained in step S2 to the other side of the umbilical cord layer, i.e., one side of the loose layer, and then covering the other side of the gel layer with the indentation surface of the second mold; that is, using two molds to press the umbilical cord layer and the gel layer in the same artificial periosteum;

[0110] S32. The compressed sample and the mold are subjected to freeze-thaw cycle treatment, vacuum freeze drying and sterilization treatment in sequence to obtain a double-layer composite artificial periosteum.

[0111] Specifically, when the sol-gel transition treatment is performed with acetic acid solution in step S23, the acidic vapor diffuses to the surface and interior of the slurry mixture from which the bubbles have been removed. At this time, the chitosan is slowly protonated and forms a physically cross-linked chitosan-sodium alginate network structure with sodium alginate through electrostatic interaction, thereby avoiding the formation of uneven precipitates or gels, and making the composite artificial periosteum have good network morphology and mechanical properties.

[0112] Specifically, in step S3, after being pressed and freeze-dried by the mold, the surface of one side of the gel layer becomes concave-convex, so that the convex structure and the concave structure are formed on the composite artificial periosteum after pressing and freeze-drying, thereby effectively increasing the degree of fit between the artificial periosteum and the part to be repaired and the contact surface area; the surface of one side of the dense layer of the umbilical cord layer becomes flat after the pressing process, and has a good mechanical barrier effect.

[0113] Specifically, in step S32, the pressed sample and the mold are frozen at -20°C for 2 hours under normal pressure, and then freeze-thawed at 4°C for 2 hours. The umbilical cord layer mainly includes collagen, polysaccharides, etc. The wet umbilical cord layer and the gel layer are subjected to freeze-thaw and pressing treatments, so that part of the gel layer can be adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, greatly improving the bonding strength between the fitting interface, thereby ensuring the stability of the structure during subsequent use, and reducing the probability of delamination of the double-layer structure.

[0114] Specifically, the sample pressed in step S32 is subjected to freeze-thaw cycles twice together with the mold, and then placed in a vacuum freeze dryer with a vacuum degree of 20 Pa, and cooled to -80°C at a rate of 10°C / min, and vacuum freeze-dried for 8 hours to obtain the composite artificial periosteum. Slowly cooling at a rate of 10°C / min can avoid damage to the tissue structure caused by too fast a temperature drop, significantly improve the drying efficiency of the repair membrane, and obtain a more uniform pore structure.

[0115] Figure 1Schematic diagram of electron microscope scanning of the longitudinal section of the double-layer structure of the composite artificial periosteum according to an embodiment of the present invention.

[0116] The composite artificial periosteum prepared in Example 1 was subjected to electron microscope scanning of the longitudinal section of the double-layer structure. Figure 1 As shown, the composite artificial periosteum is a double-layer structure. The umbilical cord layer has a dense structure and a small pore size. The umbilical cord layer retains the natural collagen fiber dense structure of the umbilical cord, which is used to face the soft tissue, is conducive to supporting the formation of soft tissue, and can effectively prevent fibroblasts and epithelial cells from growing into the bone defect area, and prevent the soft tissue from growing into the bone defect area; the gel layer has a loose structure and a large pore size. The pore size of the gel layer is larger than that of the umbilical cord layer, and has a certain roughness, which is conducive to the adhesion, proliferation and differentiation of cells. When applied to the tissue defect, it can effectively guide the regeneration of bone tissue.

[0117] The composite artificial periosteum prepared in Example 1 was placed in a simulated body fluid (SBF solution) for rehydration for 10 to 20 minutes. The composite artificial periosteum remained intact, and no stratification occurred between the umbilical cord layer and the gel layer. The rehydration experiment shows that the composite artificial periosteum prepared by the present invention can achieve the performance of not stratifying after rehydration, so that when applied to tissue defects, the dense umbilical cord layer and the loose gel layer can effectively play their respective roles.

[0118] The mechanical properties of the composite artificial periosteum prepared in Example 1 were tested according to the test conditions of the biological part 3: films and sheets in the standard GB / T5 528-2009 for the determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber and the standard GB / T1040.3-2006 for the determination of tensile properties of plastics. A total of 3 groups of samples were tested, and the test results are shown in Table 1. A total of 3 groups of samples were tested, and the test results are shown in Table 1. It can be seen from Table 1 that the average suture strength of the composite artificial periosteum is not less than 2N, the tensile strength is not less than 0.8MPa, and the tear strength is not less than 1.5N. This experiment shows that the composite artificial periosteum prepared by the present invention has good mechanical properties and can meet the strong traction effect of the tissue around the bone defect.

[0119] Table 1

[0120]

[0121] According to the general technical requirements of the standard YY / T 1794-2021 oral collagen membrane, the composite artificial periosteum prepared in Example 1 was tested for water absorption, and a total of 3 groups of samples were tested, and the test results are shown in Table 2. As can be seen from Table 2, the average water absorption multiple of the periosteum is 13.0, and the higher water absorption rate can make the periosteum fit well with the tissue, which is convenient for clinical use.

[0122] Table 2

[0123]

[0124] Active factors: The content of various factors in the umbilical cord layer and the fresh original umbilical cord prepared in Example 1. The data of various factors in the umbilical cord layer and the fresh original umbilical cord are shown in Table 3. The results show that the content of various factors in the umbilical cord membrane and the fresh original umbilical cord as raw materials is not much different, indicating that the preparation method of the composite artificial periosteum of the present invention can retain a variety of natural active factor components in the umbilical cord tissue, and has a unique biological property of promoting healing compared with simple collagen membrane or decellularized matrix products.

[0125] Table 3

[0126]

[0127] Figure 2 Schematic diagram of a mold according to a first embodiment of the present invention.

[0128] In some embodiments of the present invention, the mold is an integrated structure, and the mold includes a first surface and a second surface arranged opposite to each other. Figure 2 The first surface is an indentation surface 1, and the indentation surface 1 is provided with a convex structure (not marked in the figure) and a concave structure (not marked in the figure), and the second surface (not marked in the figure) is a smooth surface.

[0129] Figure 3 Schematic diagram of a mold according to a second embodiment of the present invention.

[0130] In some embodiments of the present invention, reference Figure 3 The mold includes a first layer 11 and a second layer 12, the first layer 11 and the second layer 12 are overlapped and fixed, the surfaces of the first layer 11 and the second layer 12 are the first surface 111 and the second surface (not shown in the figure), and the first layer 11 and the second layer 12 are woven with 316L stainless steel wire. The structure is simple, the manufacturing process is simple, the manufacturing cost is low, and the stainless steel material itself has corrosion resistance and weldability, so that the mold has good stability and plasticity, as well as high mechanical strength.

[0131] Figure 4 for Figure 3 An enlarged schematic diagram of the structure of the surface of the first layer of the mold shown; Figure 5 for Figure 3 An enlarged schematic diagram of the structure of the surface of the second layer in the mold is shown.

[0132] In some embodiments of the present invention, reference Figure 4 and Figure 5The first layer 11 is woven by dense weaving, so that the first surface 111 of the first layer 11 is an indentation surface, and the indentation surface is provided with the convex structure 101 and the concave structure 102 arranged in an orderly manner. The dense weaving means that the warp and weft have different wire diameters and different mesh counts, and the characteristics are that the warp is sparse and the weft is dense, and the warp is coarse and the weft is thin. The length direction is the warp, the width direction is the weft, and the length direction is Figure 4 The direction indicated by A is shown in the figure, and the width direction is the direction perpendicular to A. The specific structure after dense weaving is as follows Figure 5 As shown, the weaving method is conventional in the art and will not be described here. The second layer 12 is woven in a twill weaving manner, so that the second surface (not shown in the figure) of the second layer 12 is a smooth surface with a relatively flat surface and dense and small pores. The twill weaving refers to a weaving method in which each warp wire crosses above and below every two weft wires, and each weft wire crosses above and below every two warp wires. The specific structure after the twill weaving is as follows Figure 5 As shown. The first layer 11 woven by the dense weave has good acid resistance, alkali resistance and high temperature resistance, and has strong pressure resistance and wear resistance, etc.; the second layer 12 woven by the twill weave has the characteristics of flat and smooth surface, strong corrosion resistance, strong durability, etc. The first layer 11 is woven by the dense weave, so that the surface of the first layer 11 can effectively form the convex structure 101 and the concave structure 102, and the second layer 12 is woven by the twill weave, so that the surface of the second layer 12 is smooth and flat.

[0133] In some embodiments of the present invention, the warp diameter of the stainless steel wire used to weave the first layer is 0.2 mm to 0.28 mm, the weft diameter is 0.14 mm to 0.2 mm, the aperture of the first layer is 60 mesh to 100 mesh, and the thickness of the first layer is 1.2 mm to 3.4 mm. The first surface of the mold can better form the protruding structure and the concave structure, so that the protruding structure and the concave structure on the composite artificial periosteum after pressing and freeze-drying can effectively increase the degree of fit between the membrane material and the part to be repaired and the contact surface area.

[0134] In some specific embodiments of the present invention, the stainless steel wires used to weave the first layer have a warp diameter of 0.25 mm and a weft diameter of 0.18 mm, the aperture of the first layer is 80 mesh, and the thickness of the first layer is 2 mm.

[0135] In some embodiments of the present invention, the diameter of the stainless steel wire used to braid the second layer is 0.04 mm to 0.045 mm, the aperture of the second layer is 250-300 mesh, and the thickness of the second layer is 0.3 mm to 0.7 mm, so that the second surface of the second layer is relatively flat, and the apertures are dense and small.

[0136] In some embodiments of the present invention, the pore size of the second layer is 0.0446 mm to 0.0556 mm.

[0137] In some specific embodiments of the present invention, the second layer of the mold is made of stainless steel wire with a diameter of 0.042 mm plain weave, the pore size of the second layer is 0.05 mm, and the thickness of the second layer is 0.5 mm. The use of finer stainless steel wire weaving makes the pore size of the second surface of the mold dense and small, and the surface is smooth, so that the composite artificial periosteum material can be pressed into a relatively flat morphological structure.

[0138] In some embodiments of the present invention, the protruding structures and the concave structures are arranged alternately, and the spacing between adjacent protruding structures in the longitudinal direction is 0.14 mm to 0.2 mm, and the spacing between adjacent protruding structures in the latitudinal direction is 0.2 mm to 0.28 mm. The formed composite artificial periosteum has the protruding structures and the concave structures, so that it can fit closely with the tissue defect, block the entry of external soft tissue cells, play the role of isolating the soft tissue from growing into the bone defect area, and achieve a good treatment effect.

[0139] In some specific embodiments of the present invention, the protruding structures and the recessed structures are arranged alternately, and the spacing between adjacent protruding structures in the longitudinal direction is 0.15 mm, and the spacing between adjacent protruding structures in the weft direction is 0.26 mm.

[0140] In some embodiments of the present invention, the weft wire diameter of the stainless steel wire for weaving the first layer is a first wire diameter, the warp wire diameter of the stainless steel wire for weaving the first layer is a second wire diameter, the protruding structures and the recessed structures are alternately arranged, and the spacing between adjacent protruding structures in the warp direction is equal to the first wire diameter, and the spacing between adjacent protruding structures in the weft direction is equal to the second wire diameter.

[0141] In some embodiments of the present invention, the warp wire diameter of the stainless steel wire for braiding the first layer is the second wire diameter, the protruding structures and the recessed structures are arranged alternately, and the height difference between the protruding structures and the recessed structures is equal to the second wire diameter.

[0142] In some embodiments of the present invention, the protruding structures and the recessed structures are arranged alternately, and the height difference between the protruding structures and the recessed structures is 0.2 mm to 0.28 mm.

[0143] In some embodiments of the present invention, the length of the mold is 6 cm to 10 cm, the width is 4 cm to 8 cm, and the thickness is 1.5 mm to 4.1 mm. The mold is light in weight and will not damage the composite artificial periosteum when preparing it. While ensuring the pressing effect, it saves materials and reduces investment costs.

[0144] In some specific embodiments of the present invention, the mold is a thin plate structure of 8 cm×6 cm, which can not only meet the size required for the existing composite artificial periosteum compression and freeze-drying treatment, but also will not cause the composite artificial periosteum material to be compressed and deformed, and also saves freeze-drying mold production materials.

[0145] In some embodiments of the present invention, the first layer and the second layer are welded by micro-spot resistance welding or seamless butt welding, so that the mold has no protruding welding points and burrs, and the first layer and the second layer are tightly combined without gaps, and will not delaminate or fall off, and has high stability.

[0146] In some embodiments of the present invention, the first layer and the second layer both include 4 to 8 layers of stainless steel mesh. If the number of layers is too large, the air permeability and permeability are poor, which will affect the freeze-drying effect of the composite artificial periosteum. If the number of layers is too small, the overall weight is light, which will affect the pressing effect of the mold on the composite artificial periosteum.

[0147] In some specific embodiments of the present invention, the steps of preparing the mold include:

[0148] Step 1: The mold uses 316L stainless steel wire to weave two stainless steel wire meshes with different structures in a dense weave mode and a twill weave mode, and five of each are made;

[0149] Step 2: stacking and pressing five stainless steel wire meshes woven in a dense weave manner in a manner that the surfaces are flush, and then vacuum sintering to obtain the first layer body, and stacking and pressing another five stainless steel wire meshes woven in a twill weave manner in a manner that the surfaces are flush, and then vacuum sintering to obtain the second layer body;

[0150] Step three, the first layer body and the second layer body are welded by seamless butt welding technology to obtain the mold.

[0151] In some embodiments of the present invention, the surface of the 316L stainless steel wire is electrolytically polished so that it will not rust or deform during use and cleaning.

[0152] In some embodiments of the present invention, the vacuum sintering process is easy to operate, and can improve the purity of cemented carbide so that it has higher pressure resistance and good plasticity, which is convenient for subsequent processing, welding and assembly.

[0153] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A composite artificial periosteum, characterized in that: include: The cord layer is a sheet-like structure composed of umbilical cord tissue formed from the umbilical cord by mechanically removing vascular cells; as well as A gel layer adhered to one side of the umbilical cord layer, wherein the gel layer is formed by compounding chitosan and sodium alginate to form a hydrogel network and loading a bone repair mineral material and freeze-drying the material, wherein the bone repair mineral material is tricalcium phosphate; The composite artificial periosteum is placed in the SBF solution for rehydration for 10 to 20 minutes, so that the composite artificial periosteum remains intact, and no stratification occurs between the umbilical cord layer and the gel layer, achieving the performance of no stratification after rehydration; Wherein, the thickness of the composite artificial periosteum is any one of 1250 μm, 1500 μm, 1700 μm, 2000 μm, 2250 μm, 2450 μm, 2600 μm, 2800 μm, 2900 μm and 2950 μm; Wherein, the side of the umbilical cord layer facing away from the gel layer is a smooth surface, the side of the gel layer facing away from the umbilical cord layer is an indentation surface, and the indentation surface is provided with a convex structure and a concave structure; and Wherein, the umbilical cord layer is a double-layer porous structure, the umbilical cord layer includes a dense layer and a loose layer, the pore size of the dense layer is smaller than the pore size of the loose layer, the loose layer is adhered and fixed to the gel layer, and the dense layer is provided with the smooth surface; and The artificial periosteum is prepared by adhering and fixing the gel layer to the umbilical cord layer through normal pressure freeze-thaw cycle and vacuum freeze-drying.

2. The composite artificial periosteum according to claim 1, characterized in that: The particle size of the bone repair mineral material is 20 μm to 100 μm.

3. The composite artificial periosteum according to claim 1, characterized in that: The bone repair mineral material also includes silicon dioxide or bioactive glass.

4. The composite artificial periosteum according to claim 1, characterized in that: The pore size of the gel layer is 500 μm to 900 μm.

5. The composite artificial periosteum according to claim 1, characterized in that: The mass ratio of the sodium alginate, the chitosan and the bone repair mineral material is (5:5:1) to (4:2:1).

6. The composite artificial periosteum according to claim 1, characterized in that: The gel layer and the umbilical cord layer are adhered and fixed by mold pressing and freeze-drying, and the mold includes a first surface and a second surface arranged opposite to each other, the first surface is an indentation surface adapted to the indentation surface, the indentation surface is provided with a convex structure and a concave structure, and the second surface is a smooth surface adapted to the smooth surface.

7. A method for preparing the composite artificial periosteum as claimed in claim 1, characterized in that: Includes steps: Sodium alginate, chitosan and bone repair mineral materials are prepared into hydrogel by combining semi-dissolving acidified sol-gel transition method and internal gel method, and then vacuum freeze-dried after removing bubbles by ultrasonic to obtain gel layer; Providing an original umbilical cord, removing blood vessels in the original umbilical cord by mechanical means to form umbilical cord tissue to be shaped, and trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet-like structure; Adhesively fixing the gel layer to the umbilical cord layer to obtain the composite artificial periosteum; The composite artificial periosteum is placed in the SBF solution for rehydration for 10 to 20 minutes, so that the composite artificial periosteum remains intact, and no stratification occurs between the umbilical cord layer and the gel layer, achieving the performance of no stratification after rehydration; and Wherein, the thickness of the composite artificial periosteum is any one of 1250 μm, 1500 μm, 1700 μm, 2000 μm, 2250 μm, 2450 μm, 2600 μm, 2800 μm, 2900 μm and 2950 μm.

8. The method for preparing the composite artificial periosteum according to claim 7, characterized in that: The step of preparing the hydrogel by combining the semi-dissolving acidified sol-gel transition method and the internal gel method with sodium alginate, chitosan and bone repair mineral material comprises: Adding the bone repair mineral material into deionized water and stirring to prepare a bone repair mineral solution; Adding the sodium alginate and the chitosan to the bone repair mineral solution in sequence, and stirring to mix them evenly to obtain a sol solution; The sol solution is exposed to an acidic environment for gelation to obtain the hydrogel.

9. The method for preparing the composite artificial periosteum according to claim 7, characterized in that: The step of adhering and fixing the gel layer to the umbilical cord layer to obtain the composite artificial periosteum comprises: In an environment with a temperature of 11°C to 15°C, one side of the dense layer in the umbilical cord layer is covered on the smooth surface of the mold, one side of the gel layer is adhered to one side of the loose layer in the umbilical cord layer, and the other indentation surface of the mold is covered on the other side of the gel layer.

10. The method for preparing the composite artificial periosteum according to claim 9, characterized in that: The step of adhering and fixing the gel layer to the umbilical cord layer to obtain the composite artificial periosteum also includes a normal pressure freeze-thaw cycle step and a vacuum freeze-drying step; The normal pressure freeze-thaw cycle step comprises: freezing the mold sandwiched with the umbilical cord layer and the gel layer at a temperature not higher than -22°C for not less than 2 hours at normal pressure, and then freezing and thawing at a temperature not higher than 10°C for not less than 2 hours, and performing freeze-thaw cycles 1-3 times to obtain a periosteum sample; The vacuum freeze drying step includes: placing the periosteum sample in a vacuum freeze dryer, cooling it to -80±5°C at a rate of 5°C / min to 10°C / min, and the vacuum freeze drying time is not less than 8 hours to obtain the composite artificial periosteum.

11. The method for preparing the composite artificial periosteum according to claim 10, characterized in that: Repeat the steps of covering one side of the dense layer in the umbilical cord layer on the smooth side of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer, and stacking 2 to 6 layers of the umbilical cord layer and the gel layer in the stacking order of the mold, the umbilical cord layer, the gel layer and another mold to obtain 2 to 6 layers of the artificial periosteum.

12. The method for preparing the composite artificial periosteum according to claim 7, characterized in that: The step of trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure comprises: In an environment with a temperature of 11°C to 15°C, the umbilical cord tissue to be shaped is cleaned with a cleaning solution, trimmed into sheets and cleaned with deionized water for 1 to 3 times to obtain the umbilical cord layer, and the cleaning temperature is 11°C to 15°C and the cleaning time is 15 to 20 minutes.

Citation Information

Patent Citations

  • Double-layer artificial periosteum, preparation method and application thereof

    CN114028619A

  • Active biological patch and preparation method thereof

    CN111330077A

  • Preparation method of bone repair scaffold

    CN115282335A